IMPROVING STUDENTS’ ORAL PRESENTATION PERFORMANCE THROUGH THE USE OF VISUAL MEDIA IN SMALL GROUP DISCUSSION - Audi Yundayani; dian kardijan (STIBA IEC JAKARTA, 2018)
Oral presentation as a part of academic speaking is required by the students in university level. However, students having problem in perform it due to lack of self confidence and lack of ideas to be presented. The aim of the research is to improve students’ oral presentation performance by using visual media in small group discussion at STKIP Kusumanegara. The research method is a action research to show visual media using in solving students’ oral presentation problem. Techniques for data collection are through observation, speaking test, interview, and documentation. The result of the research shows significant improvement in student’ oral presentation performance. Through small group discussion, visual media using can support students to emerge several ideas during the oral presentation. Due to media support, students are being able to overcome their speaking anxiety. By the end, the result showed that visual media using through small group discussion can be an alternative way to improve students’ oral presentation performance